Objectification and Physical Appearance in Adolescent Girls - L.T. David; T. David (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Objectification, understood as internalization of an external observer's perspective of their own bodies, is a phenomenon experienced by females. The present research focuses on examining the relationships among sexual objectification, body shame, body appearance anxiety, fear of negative evaluation, and eating attitudes in dancer and non-dancer adolescents. The results revealed no significant differences between the two groups. However, sexual objectification was found to be associated with body shame, eating attitudes, and fear of negative evaluation.